Acceleration of the thermal decomposition of RDX in microdroplets investigated by aerodynamic thermal breakup droplet ionization mass spectrometry. Issue 3 (27th October 2020) - Pervukhin, Viktor V.; Sheven, Dmitriy G.
Abstract: The thermal decomposition of RDX in microdroplets in the heated capillary was investigated by Aerodynamic Thermal Breakup Droplet Ionization (ATBDI) mass spectrometry. The kinetic parameters of the thermal decomposition of RDX in water droplets were estimated. The suction capillary of the ATBDI setup was considered as a flow reactor of ideal displacement. In water droplets, the activation energy of the reaction turns out to be 2-4 times smaller than in the gas and bulk solution, indicating the catalytic role of droplets. Copyright © 2020 American Association for Aerosol Research